Every duke has his day - Enoch, Suzanne (St. Martin's Griffin, 2023)
"Michael Bromley, Duke of Woriton, has a passion, but it's not for chasing ladies or gambling till dawn. No, his is the far more dangerous pursuit of the science of chemistry. He may be a tad eccentric, but he can navigate a society ballroom, and manage a polite conversation--if he must. He's certainly capable of taking care of his aunt's perfectly behaved poodle, Lancelot, while she's on holiday. Elizabeth "Bitsy" Dockering, third daughter of a viscount, is enjoying her second, spectacular Season in London. She is a Diamond of the Season and is adored by all--and especially by her precious black poodle, Galahad. To everyone else, however, Galahad is a demon dog. So much so that Bitsy's most insistent beau and particular victim of Galahad's bad manners, has hired a thief to steal the dog, clearing the way for his suit. But none of them can plan for a chaotic encounter in the park, resulting in lost notes, a soaking in the Serpentine and an accidental dog swap... and Lancelot being kidnapped instead of Galahad! Determined to locate the dog, Michael isn't thrilled to be saddled with a flighty female insisting on helping--except that Bitsy has a great deal more sense than he expected. And a sharp tongue to match. Still, what's a scientist to do but continue to pursue an outcome, however unexpected it may be?"--